Peran Dewan Adat Suku Sentani untuk Penyelesaian Konflik Kekerasan dalam Rumah Tangga - Christine O. I. Sanggenafa; Irwan Martua Hidayana (CENDERAWASIH: Jurnal Antropologi Papua, 2020)
This article aims to describe and analyze the role of the Sentani Ethnic Council in the resolution of domestic violence experienced by Sentani women. Sentani society acknowledges that Sentani Tribal Council established in has several functions in political, economic, legal, security, and religious affairs. This study focused on the Sentani Tribal Council as a legal institution in solving domestic violence against Sentani women. The research problem is what factors encourage Sentani women to choose to resolve domestic conflicts through Sentani Tribal Council. This is a qualitative research that employed in-depth interview techniques and observation in the Sentani Ethnic Council courts. Interviews were carried out to victims of domestic violence, head of tribal council, and community leaders, domestic violence doer, and Sentani people. Sentani women who were victims of domestic violence went to the Sentani Ethnic Council to solve their problems due to several reasons, namely peaceful court, customary fine, and avoiding shame. There is a change in the customary fine from certain goods to rupiah currency. Although Sentani women obtained conflict resolution in the Sentani Ethnic Council, it did not provide justice yet. There are different views on domestic violence in Sentani. Some parties local government, church, tribal council, women, and victim perceived that domestic violence is violating human rights, therefore, must be sentenced. While the doers and young men in Sentani perceived that violence against women is common in their culture. From an anthropological perspective, domestic violence in Sentani is a debate between culture and rights in the context of cultural relativism.